Ibrutinib Treatment of a Patient with Relapsing Chronic Lymphocytic Leukemia and Sustained Remission of Richter Syndrome. (November 2017) - Albi, Elisa; Baldoni, Stefano; Aureli, Patrizia; Dorillo, Erica; Del Papa, Beatrice; Ascani, Stefano; Di lanni, Mauro; Falzetti, Franca; Sportoletti, Paolo
Purpose: Richter syndrome (RS) is a rare event in chronic lymphocytic leukemia (CLL) that is influenced by biological factors and prior CLL treatments. Ibrutinib is a Bruton tyrosine kinase inhibitor that has shown remarkable efficacy in CLL; however, little is known about its relationship to RS. We report a case of ibrutinib efficacy against CLL in a patient with prolonged remission of RS. Methods: The patient was diagnosed with CLL in 2003. Biological findings at onset included absent ZAP70 expression, mutated IGVH, and NOTCH1 mutation. He was treated with FCR with partial response. In 2013, he progressed to RS, not clonally related to the underlying CLL. The patient was treated with anthracycline- and platinum-based regimens, obtaining a complete remission. After 3 years, he presented a CLL progression with worsening lymphocytosis, anemia, thrombocytopenia, increased splenomegaly, and lymphadenopathies. Positron emission tomography-computed tomography scan excluded pathologic uptake. Thus, he was started on ibrutinib. Results: At 12 months' follow-up, we observed white blood cell normalization, increased hemoglobin and platelet levels, disappearance of lymphadenopathy, and spleen size reduction. Therapy was well-tolerated with no evidence of RS. Conclusion: This case demonstrates sustained RS remission in a patient with CLL under ibrutinib therapy, thus improving our knowledge on the use of this new drug in CLL and beyond.